Fair Trade - Palafox, Carlos German (Archives of Business Research, 2017)
Economic integration, which took place through the North American Free Trade Agreement (NAFTA) is creating winners and losers in our country. The winners are the transnational corporations and the large private agricultural producers; the losers are the indigenous communities, peasantry, cooperatives, and the small and medium-sized farmers in the areas which are the most poor of the country. The objective of this study is to analyze to the social producers, which are grouped in an area of common land called “Ejido Etchohuaquila”, located in the municipality of Navojoa, Sonora Mexico which has been integrated to Fair Trade as an alternative markets, producing organic products. In addition to this study, we analyze the protocols that were fulfilled for joining this network. Furthermore we assess the community development in terms of social welfare and social cohesion, also we highlights the progress of this community that was one of the communities most impoverished region, without access to development before to become a member of the international circuit.